Sustainability-driven marketing education: assessing the role of perceived marketplace influence on consumption patterns in private Egyptian universities - Sara Mohamed Abdelaziz El-Menawy (Future Business Journal)
Abstract He dynamic field of marketing plays a pivotal role in shaping consumer behavior and influencing product choices. Integrating sustainability into marketing education can provide students with a deeper understanding of sustainable consumption and its broader implications for the marketplace. Despite growing scholarly interest in sustainability and consumption, limited research has explored how embedding sustainability concepts within marketing curricula impacts students’ consumption behaviors, particularly in developing contexts. This study addresses this gap by examining the relationship between sustainability marketing education and sustainable consumption, while also investigating the moderating role of perceived marketplace influence. Drawing on data collected from a survey of 422 students at private Egyptian universities, the study employs a conceptual framework to assess how educational exposure to sustainability in marketing influences behavioral outcomes. The findings reveal that sustainability education in marketing significantly enhances students’ awareness and practice of sustainable consumption. Moreover, the perceived marketplace influence plays a critical moderating role, amplifying the impact of education on students’ behavioral intentions. These insights underscore the value of sustainability-focused marketing education in promoting responsible consumption and highlight the importance of contextual market factors in shaping these educational outcomes.